A Newly Isolated Bacillus subtilis Strain Named WS-1 Inhibited Diarrhea and Death Caused by Pathogenic Escherichia coli in Newborn Piglets - Du, Yunping; Xu, Zhichao; Yu, Guolian; Liu, Wei; Zhou, Qingfeng; Yang, Dehong; Li, Jie; Chen, Li; Zhang, Yun; Xue, Chunyi; Cao, Yongchang (Frontiers in Microbiology, 2019)
Bacillus subtilis is recognized as a safe and reliable human and animal probiotic and is associated with bioactivities such as production of vitamin and immune stimulation. Additionally, it has great potential to be used as an alternative to antimicrobial drugs, which is significant in the context of antibiotic abuse in food animal production. In this study, we isolated one strain of B. subtilis, named WS-1, from apparently healthy pigs growing with sick cohorts on one Escherichia coli endemic commercial pig farm in Guangdong, China. WS-1 can strongly inhibit the growth of pathogenic E. coli in vitro. The B. subtilis strain WS-1 showed typical Bacillus characteristics by endospore staining, biochemical test, enzyme activity analysis, and 16S rRNA sequence analysis. Genomic analysis showed that the B. subtilis strain WS-1 shares 100% genomic synteny with B. subtilis with a size of 4,088,167 bp. Importantly, inoculation of newborn piglets with 1.5 × 1010 CFU of B. subtilis strain WS-1 by oral feeding was able to clearly inhibit diarrhea (p < 0.05) and death (p < 0.05) caused by pathogenic E. coli in piglets. Furthermore, histopathological results showed that the WS-1 strain could protect small intestine from lesions caused by E. coli infection. Collectively, these findings suggest that the probiotic B. subtilis strain WS-1 acts as a potential biocontrol agent protecting pigs from pathogenic E. coli infection. Importance: In this work, one B. subtilis strain (WS-1) was successfully isolated from apparently healthy pigs growing with sick cohorts on one E. coli endemic commercial pig farm in Guangdong, China. The B. subtilis strain WS-1 was identified to inhibit the growth of pathogenic E. coli both in vitro and in vivo, indicating its potential application in protecting newborn piglets from diarrhea caused by E. coli infections. The isolation and characterization will help better understand this bacterium, and the strain WS-1 can be further explored as an alternative to antimicrobial drugs to protect human and animal health.